The Influence of Inaportnet Skills and Employee Performance on the Smoothness of Ship Services at PT Benua Indah Gemaca Banten Branch - Jasief Soetopo Putrahardja; Muhammad Kemal Passya; Vidya Selasdini (Journal of Accounting and Finance Management, 2022)
In general, it can be said that regular shipping is a reflection of a shipping policy that can harmonize the relationship between operators and users of sea transportation services, both in terms of service products and handling of goods. The concept that leads to choosing any product that can provide satisfaction is value, where the value itself is a consumer's estimate of the product's capacity to satisfy various goals. But unfortunately, the export-import transportation activities are currently still dominated by companies. This can be seen from the increase in shipping companies, both national and foreign, the consequence of which is the emergence of competition among shipping companies. For the smooth operation of loading and unloading of imports or exports, it is necessary for the carrier/ship owner as well as the customer/user of the goods delivery service. To realize this smoothness, in carrying out the activities of the shipping company, it can appoint agents at the port where the ships will visit to carry out activities. Procedurally, the shipping company appoints a general agent in a certain maritime capital in the country that will be visited by the ship in order to carry out loading and unloading activities. Unloading and loading activities. So that general agency companies that have been appointed as representatives can improve services to attract customers. The port agent's task is to serve the ship and submit documents for when the ship has docked and left in the port area of ??PT. Pelindo II Banten Branch, Inaportnet is a system that combines, among others, a traffic and sea transportation information system, an online ship system, a seafarer certificate application, a port information system, and a port business entity system, PT. Benua Indah Gemaca is a ship agency that uses the Inaportnet service system. Mastering technology and communication is very important in document services with KSOP and other related agencies. The problem that arises with the implementation of the Inaportnet system is that some employees do not master Inaportnet technology, this will hamper ship document services and cause the company to pay more than it should to pay for human resources from outside who understand Inaportnet technology.